PENGEMBANGAN BUKU PENDIDIKAN SEKSUAL PADA PESERTA DIDIK KELAS VI - Ageng Saputri, Aprilia; Agus Wibowo; Siti Nurlaila (Counseling Milenial (CM), 2024)
The purpose of the development of this research is to produce a product in the form of a sexual education book for grade VI students at SD Negeri 1 Telogorejo by developing several aspects including development procedures, book feasibility, book attractiveness and book effectiveness. The type of research used is research and development with the ADDIE development model. The instruments used in this study were a sexual education knowledge questionnaire, expert validation sheets (material, media and language), product practicality sheets by students. The results obtained from this study are (1) the development procedure using the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The researchers used these stages for the development of sexual education books so that they could produce appropriate products. (2) The media of sexual education books is included in the very appropriate category for use. This was obtained by the researchers based on an average feasibility of 86.2% obtained from the assessment of experts and students. (3) The media of sexual education books is able to provide an attraction so that students are enthusiastic in following the learning process and actively participate in learning activities. This the researcher knows based on the observations that the researcher made during the process of learning activities. (4) Based on the test results, the sexual education book media has good quality from the visual aspect, the content and the language applied is feasible to use.